The FBI way: inside the bureau's code of excellence - Figliuzzi, Frank (Custom House, 2022)
Introduction: hot wash -- Code -- Conservancy -- Clarity -- Consequences -- Compassion -- Credibility -- Consistency -- Epilogue: ops plan.